Unidade de Planejamento Participativo - UPP: divisão territorial na Região da Subprefeitura Capela do Socorro (Município de São Paulo) - Adam, Pedro Nadal (2005)
The proposition of the present study is to show a territorial division of districts, named UPP - Participative Planning Unit, adopted since 2002 in the Subprefeitura Capela do Socorro, in the City of São Paulo. The UPP is based on the research Origem-Destino (departure-arrival), created by the METRO (Subway Company of the State of São Paulo) for planning urban transport in the Metropolitan Region of São Paulo. This study is divided in three chapters. The first and the second ones gives a general overview of the economic influences on the occupation of space in the City of São Paulo. For that purpose we used the history of land occupation in the City of São Paulo, and theories related to space organization. The third part of this study presents the UPP. This methodology is based upon a territorial division simultaneously small enough for people to identify in their daily life, and big enough to involve dense social and economic activities demanding urban planning. The territorial divisions have generally been seen from the angle of public management. The UPP territorial division allows effective people\'s participation, in that sense the UPP proposition is closer to the main aspects of daily life of the common people, and facilitates the understanding of the local without losing the angle of public management. It\'s the quest for a territorial division able to bond the population by the understanding of the locus, in a participatory process.